Laparoscopic Subtotal Gastrectomy and Sigmoidectomy Combined With Natural Orifice Specimen Extraction Surgery (NOSES) for Synchronous Gastric Cancer and Sigmoid Colon Cancer: A Case Report - Zhu, Qingshun; Yu, Lei; Zhu, Guangxu; Jiao, Xuguang; Li, Bowen; Qu, Jianjun (Frontiers in Surgery, 2022)
Background: Gastric cancer and colon cancer are rarely seen in clinic, but there are still related reports. For gastric cancer and simultaneous colon cancer, surgical resection is the main treatment. Traditional surgery requires an incision from xiphoid process to pubic symphysis. With the progress of minimally invasive technology, laparoscopic surgery is also used in the treatment of gastric cancer, but also in the abdominal incision to remove specimens and in vitro anastomosis of digestive tract. Taking specimens through the natural cavity as a new surgical method can not only reduce the abdominal incision, but also reduce the occurrence of wound-related complications. Here, we report a patient with gastric cancer and colon cancer who was treated in our hospital. Case Summary：We report a series of patients with gastric cancer and colon cancer. upper abdominal pain was treated in our hospital for 6 months. electronic gastroscopy showed large irregular ulcers on the lesser curvature of the gastric antrum and biopsy showed poorly differentiated adenocarcinoma of the gastric antrum. The enhanced CT of abdomen and pelvis showed irregular thickening of gastric antrum wall, irregular thickening of sigmoid colon wall and no obvious enlarged lymph nodes around. Further electronic enteroscopy showed that the sigmoid colon showed cauliflower protuberance, the intestinal cavity was slightly narrow, the intestinal wall was stiff, and the biopsy pathology showed moderately differentiated adenocarcinoma of the sigmoid colon. No obvious abnormality was found in serological tumor indexes. We diagnosed gastric cancer with sigmoid colon cancer and the patient received Laparoscopic subtotal gastrectomy and sigmoidectomy combined with natural orifice specimen extraction surgery. At present, 12 months after operation, no clear tumor recurrence was found in the metastasis. Conclusion: We should improve the understanding of gastric cancer and sigmoid cancer and combine examination with pathology to avoid misdiagnosis as metastatic cancer. Laparoscopic subtotal gastrectomy should be performed for tumors with no serosa invasion, body mass index < 30 and tumor diameter < 6.5cm. Sigmoidectomy combined with natural nostril sampling is feasible.